Close enough to touch - Dahl, Victoria (Harlequin HQN romance, 2012)
Leaving her job as a Hollywood makeup artist behind, Grace Barrett arrives in Jackson Hole, Wyoming, to stay with her great aunt to figure out her life and finds herself distracted by Cole Rawlins, a rugged cowboy.